A Study Of Coastline Change In Kuching And Kota Samarahan Division Using Geographic Information System - Foo, Phang Wee (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Coastal erosion often occurs in our country at different rate and brought adverse impact to the environment as well as properties. In Sarawak, coastal erosion problem experienced by the coastal community was frequently reported in the Medias. It proved that the coastal erosion is a serious issue in our country. In this study, a GIS based Coastal Information System is developed for both Kuching and Kota Samarahan Divisions. This database system is able to perform several analyses dealing with coastal zone monitoring such as producing erosion and sedimentation map, identifying the amount of changes of the coastline and modeling the future behavior of the coastline in other to identify the potential risk villages. GIS software used in this study is ESRI's ArcView GIS 3.